A New Algorithm Technique for Protection Secure Personal Key and Cloud Storage - Waleed Abdulqahar, Assma (ExcelingTech, 2020)
Abstract People can only enjoy the completed advantages over astronaut computing condition we may address the entirely actual privateness or safety concerns that arrive with storing touchy private facts into databases and applications measure around the Internet. Cloud computing is the class of a computing rule the place the enormous dynamic up to expectation IT helps as like a